First Year Hons. Mention: Out of the Park: HREQ 1900, Sexuality, Gender, and Society. CD: Tom Hooper. - Blacha, Stefan (Noteworthy: The LA&PS Writing Prizes, 2023)
In the thought-provoking and beautifully written critical analysis “Out of the Park: A Creative Work and Reflection on Baseball’s Subordinate Masculinities”, the author seamlessly weaves an informative and in-depth discussion of the startlingly few professional baseball players who have “come out” as gay with the author’s own self-reflections. By combining detailed research with thorough analysis, the author helps us to realize the significance of the courageous actions of a few gay baseball players, as we wonder how many continue to conceal their true sexuality. As a result, the reader finds themselves inevitably considering their own connection to the sport and their own complicity with the sport’s heteronormativity, let alone with the superficial response of the baseball industry itself. This exceptionally well-crafted, thoroughly researched and wonderfully lucid analysis and reflection is certainly most worthy of a first-year writing award.